2019
DOI: 10.1007/s40097-019-00316-x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of monodispersed and cytotoxic silver nanoparticles using Launaea taraxacifolia leaf extract

Abstract: The current work investigated the green and low-cost preparation of silver nanoparticles (AgNPs) using the aqueous extract from Launaea taraxacifolia leaf and studied its antimicrobial effects. The leaf extract was analysed in a gas chromatogrammass spectrometer to assess the phytochemicals present. UV-Vis spectrophotometer was used to monitor the formation of AgNPs, the morphological assessment was performed by a scanning electron microscope, energy dispersive X-ray analysis was used to determine the elementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Post overnight incubation at 37 °C, the lowest concentration of each antibiotic that showed no observable growth was considered as the MIC. MBC was determined via inoculating 20 µl out of wells showing no growth on agar plates followed by incubation at 37 °C for 24 h. Minimum bactericidal concentration (MBC) is the minimum antibiotic concentration that showed no obvious growth [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Post overnight incubation at 37 °C, the lowest concentration of each antibiotic that showed no observable growth was considered as the MIC. MBC was determined via inoculating 20 µl out of wells showing no growth on agar plates followed by incubation at 37 °C for 24 h. Minimum bactericidal concentration (MBC) is the minimum antibiotic concentration that showed no obvious growth [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…This was repeated thrice to increase the purity of the particles. The wet particles were dried in an oven at 60°C for 2 h. Finally, the particles were stirred in absolute ethanol to reduce aggregation and then dried at 60°C for 30 min in an oven to expel the solvent [18].…”
Section: Synthesis Of Agnpsmentioning
confidence: 99%
“…5). It showed major transmission peaks at 3186 cm -1 corresponding to N-H or O-H stretching vibration of aromatic compounds [37,38], 2918 cm -1 stretch ascribed to C-H stretch of alkanes [18]. Additional peaks were observed at 2117 cm -1 considered for the C=C stretching vibration of alkyne, the one near 1596 cm -1 was attributed to N=N bond while that around 1030 cm -1 was the bending vibration of C-O bond.…”
Section: (Ftir) Of the Agnpsmentioning
confidence: 99%
“…This demonstrates that the plant possesses a broad spectrum potency against gram-positive and gram-negative bacteria. Moreover, Essien et al, 13 also demonstrated that the silver nanoparticles synthesized using the leaf extract of Launaea taraxacifolia exhibited high potency against P. aeruginosa and P. mirabilis at low concentrations. However, there is a dearth of information on the effect of AgNPs synthesized using Launaea taraxacifolia in fish preservation.…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, the inherent biomolecules in plants serve as natural capping agents, which prevent oxidation of the synthesized NPs. 13 Launaea taraxacifolia of the family Asteraceae used for this study is a green leafy vegetable (Figure 1) locally cultivated and widely consumed in Nigeria, Senegal, Ghana, Dahomey, and Sierra Leone. 14 It is also known as African lettuce or wild lettuce.…”
mentioning
confidence: 99%